MOLECULAR AND COMPOUND-SPECIFIC HYDROGEN ISOTOPE ANALYSES OF INSOLUBLE ORGANIC MATTER FROM DIFFERENT CARBONACEOUS CHONDRITE GROUPS - Wang Y.; Huang Y.; Alexander C.M.O.D.; Fogel M.; Cody G. (My University, 2005)
We have conducted the first systematic analyses of molecular distribution and δD values of individual compounds in pyrolysates of insoluble organic matter (IOM) from different carbonaceous chondrite groups, using flash pyrolysis coupled to gas chromatography-mass spectrometry and compound-specific D/H analysis. IOM samples from six meteorites of different classifications, Elephant Moraine (EET) 92042 (CR2), Orgueil (CI1), Allan Hills (ALH) 83100 (CM1/2), Murchison (CM2), ALH 85013 (CM2), and Tagish Lake (C2) were isolated and studied. Except for the pyrolysate of Tagish Lake IOM, pyrolysates of all five meteorite IOM samples were dominated by an extensive series of aromatic (C1 to C7 alkyl-substituted benzenes, C0 to C2 alkyl-substituted naphthalenes), with aliphatic (straight chain and branched C10 to C15 alkanes) hydrocarbons and several S- and O- containing compounds (C1 to C2 alkylthiophenes, benzothiophene, benzaldehyde) being also present. The strong similarity in the pyrolysates of different carbonaceous chondrites suggests certain common characteristics in the formation mechanisms of IOM from different meteorites. The Tagish Lake IOM sample is unique in that its pyrolysate lacks most of the alkyl-substituted aromatic hydrocarbons detected in other meteorite IOM samples, suggesting distinctively different formation processes. Both bulk δD values of meteorite IOMs and weighted-average δD values of individual compounds in pyrolysates show a decreasing trend: CR2 > CI1 > CM2 > C2 (Tagish Lake), with the EET 92042 (CR2) IOM having the highest δD values (∼2000‰ higher than other samples). We attribute the high D contents in the IOM to primitive interstellar organic sources.